A note on Allen-Uzawa partial elasticities of substitution: the case of the translog cost function - Atanas Christev; Allen Featherstone (Institute for the Study of Labor (IZA), 2007)
This note provides a useful property of the Allen-Uzawa partials for the translog cost function. It also suggests how the main results extend to any functional form with certain properties. The curvature of the Allen-Uzawa matrix is the same as the curvature of the Hessian matrix. Intuitively and empirically, the Allen-Uzawa partials allow for the verification of curvature properties.
urn:nbn:de:101:1-2008041059
Keywords: 330; Kostenfunktion; Substitutionselastizität; Marginalanalyse; Theorie